Avatars In the work of the painter "Mahmoud Fahmy" (Journal of the College of Basic Education, 2022)
The tagged study (symbolic indications in the works of the painter "Mahmoud Fahmy") represents a modest scientific effort to reveal the technical aspects of the uses of (symbol) in the works of the artist "Mahmoud Fahmy", as well as to reveal its formal uses and the resulting expressive indications, which prompted the researcher to Collecting scientific materials and dealing with them to serve the research topic, through a study that included three chapters. The first chapter included (the methodological framework of the research), including the research problem, its importance and its objectives, which were summarized by (disclosure of the technical aspects of employing the symbol in the artistic forms of the painter "Mahmoud Fahmy", as well as revealing the symbolic - expressive - connotations - of the artistic forms employed in the painter's paintings." Mahmoud Fahmy"). Also, this chapter included the limits of the research (objective, temporal, and spatial), and finally, the definition of the most important terms contained therein. The second chapter of this study contained the (general) theoretical framework in which the researcher dealt with a number of topics, including the subject of the artistic symbol and its expressive connotations. As well as a brief overview of the life of the artist "Mahmoud Fahmy" and his artistic career. The general framework of the search resulted in a number of indicators, including:1 For every plastic artwork there are two types of symbolic connotations that directly and effectively control the process of producing it as an integrated creative artwork, namely the subjective (closed / which is the subject actually displayed) and the general (the open / the suggested subject).2 The recipient's emotional connotations are achieved through the direct symbolic excitement of any artwork, as it is directly related to the psychological state of the artist as well as the viewer, alike.3- Beauty has a semantic-emotive power, which results in a kind of pleasure aroused by a person who is sensitive to beauty. It refers exclusively to immediate and direct emotions when we see an exciting aesthetic scene.4- When we see symbolic signs or signs that have been agreed upon in advance - a kind of emotional feeling - the agreement is generated for us even if it is contrary to reality and custom. As for the third chapter of the research, the researcher dealt with the procedures that included (the research community, the method of selecting samples, the research method, the tool, and finally the analysis of the research samples identified by the researcher with three samples (artistic paintings) by the painter “Mahmoud Fahmy”, which resulted in a number of results. Of which :1- The artist relied on the realistic-symbolic style in embodying his artistic forms, by projecting his symbols onto certain parts of his formal uses, giving the symbol an intuitive and interrogative dimension that allowed the recipient to analyze the symbolic ciphers and identify the meanings of the expressive work.2 In order to move the plastic painting from the subjective (closed) system to the general (open) system, the artist resorted to establishing symbolic-explaining connotations through which he linked what is inside the borders of the painting with what is outside, and what is sensual with intuitive3 The artist "Mahmoud Fahmy" sought to activate symbolic connotations stemming from the inspiration of imagination through direct symbolic connotations, which he wanted to simulate the world of imagination and dreams.